Metodologia de delimitação de área de influência e elaboração de modelo de geração de viagens para supermercados de cidades de médio porte - Freitas, Gabriel Vendruscolo de (2009)
The study of Trip Generating Centers and impacts caused by the implementation of these developments for the population of a city, both the highway system, as in the use and occupation of land is important to ensure the sustainable development of urban society. Supermarkets are developments that concentrate a wide variety of products and services attracting a large demand for trips, thus causing impacts on the urban road system. These projects have been studied as Trip Generating Centers in countries like the United States, Argentina and Brazil, however, this work presents a new approach, choosing the Brazilian cities of medium size. With the summary of existing literature on the subject, is proposed: a new methodology for defining the influence area, which considers the potential for attracting new development and its competitors in a geographic information system, and generating models trips to modals other than motor vehicles and no motor vehicles, using simple and multiple linear regression.